(untitled) (Balneo and PRM Research Journal, 2024)
Spondylolisthesis represents the slippage of one vertebra over another, and is widely diagnosed among patients accusing low back pain. Despite most patients being asymptomatic, spondylolisthesis can be the cause of extremely severe, irreversible, and invalidating symptoms. The most frequent types of spondylolisthesis are isthmic, degenerative, dysplastic, traumatic, pathologic, and iatrogenic. While numerous classification systems have been used to describe spondylolisthesis, the descriptive Wiltse classification and the Meyerding classification based on the severity of slippage are the most commonly used in current practice. The clinical evaluation is focused on the degree of pain, the presence of radiculopathy, and other neurological deficits, and is followed by diagnostic imaging, including standing anteroposterior and lateral spine radiographs, computed tomography, and magnetic resonance imaging. Therapeutic options include conserva-tive methods comprising symptomatic medication and physical therapy for lowgrade spondy-lolisthesis with good to excellent results in the long term, as well as surgical treatment with a variety of possible techniques that allow for the reduction of the grade of slippage and obtaining the fusion of the affected level, followed by a well-tailored physical therapy program. The most important role for a patient’s long-term satisfactory result is adequate medical rehabilitation, with consequent and properly designed regimens that the patients will adhere to for the rest of their lives.